Peran PPAT Dalam Melindungi Hak Kepemilikan Tanah Di Indonesia - Ubaidillah (CV. ITTC INDONESIA, 2024)
This research aims to examine the role of Land Deed Officials (PPAT) in protecting land ownership rights in Indonesia. The research method used is qualitative, with a case study approach to gain an in-depth understanding of the role of PPAT. Data was collected through in-depth interviews with PPAT, land owners and other relevant stakeholders. The research results show that PPAT has a key role in protecting land ownership rights by carrying out the process of making legal land deeds and following applicable regulations. However, there are still several challenges such as a lack of public awareness of the importance of PPAT in land transactions and PPAT compliance with professional ethics.